O impacto do argumento ecológico nas atitudes dos consumidores - um estudo experimental - Pereira, Severino Joaquim Nunes (2003)
An increasing interest in society towards environmental and ecological issues have beaconed consumer¿s behavior research, particularly the ones related to the identification of the impact of environmental agendas on consumer habits. The objective of the present study is to attitudes related to brands, advertising and purchase intention. The study was based on data gathered through a ¿between subjects¿ experimental research, with three levels of manipulation. One hundred and sixty eight students from the city of Rio de Janeiro were selected for the experiment. The hypothesis suggested that subjects who were exposed to ecological cues demonstrate a more favorable behavior towards advertising attitude (H1A), brand attitude (H1B) and purchase intentions (H1C) than the ones who were not. In addition, an intrinsic health cue called ¿Omega 3¿ was introduced to the experiment to enhance the results of the research. The results have shown that subjects are indifferent to ecological cues regarding their attitudes towards the advertising and purchase intention. However, the study determined a more favorable attitude towards the brand by subjects exposed to the ecological cue. Therefore, it is possible to conclude that although ecological cues exposed in advertisements do not result on an increase of a positive of the product label is enhanced positively due to the relation of the brand with environmentally sound practices.